Analisis Komparatif Rasio Likuiditas, Aktivitas, Solvabilitas dan Profitabiltas PT.Sariguna Primatirta dengan Industri AMDK 2020-2024 - Paramadharma, Harnandito; Habibie; Kurnia Rambe; Sri Hermuningsih (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2025)
This study compares the financial performance of PT. Sariguna Primatirta (CLEO) to its competitors (ADES & MYOR) in the bottled drinking water (AMDK) business in Indonesia from 2020 to 2024. The analysis methodologies employed include the calculation of liquidity, activity, solvency, and profitability ratios, as well as trend analysis, stability tests (standard deviation), and benchmarking. The study's findings show that while PT. Sariguna Primatirta's profitability and activity performance are high, company has a low liquidity ratio. In comparison to the industry/competitors, PT. Sariguna Primatirta's liquidity is lower, the activity ratio is superior in the accounts receivable and inventory turnover ratios, but the accounts receivable turnover decreases, the solvency ratio is stable but the trend is below the industry, and the profitability ratio is above the industry average.